Evaluation of early-generation tropical maize testcrosses for grain-yield potential and weevil (Sitophilus zeamais Motschulsky) resistance. (January 2021) - Sserumaga, Julius P.; Makumbi, Dan; Oikeh, Sylvester O.; Otim, Michael; Machida, Lewis; Anani, Bruce Y.; Nhamucho, Egas; Beyene, Yoseph; Mugo, Stephen
Abstract: Smallholder maize farmers in Africa experience pre- and post-harvest production stresses either individually or in combination at different stages of the crop cycle. The maize weevil is among the major post-harvest storage pests. A strategy to address this problem is to develop and promote high yielding maize germplasm with resistance to multiple stresses. A study was conducted to: 1) assess yield and agronomic performance of testcross hybrids developed from early generation lines; and 2) assess the response of the testcross hybrids to infestation with Sitophilus zeamais. Fifty-eight drought-tolerant testcross hybrids were evaluated for agronomic performance and weevil resistance at four environments in Uganda in 2016. Hybrid G39 (L2/T2) had the best grain yield performance; it significantly out-performed the best check by 11.4% in all environments. Hybrid grain from field trials was subjected to Sitophilus zeamais infestation in a choice and no choice test under laboratory conditions. Hybrids G56 (L49/T2) and G58 (L51/T2) had the least weevil damage and were rated as resistant to Sitophilus zeamais . The numbers of damaged kernels, number of exit holes and ear aspect were positively correlated with the grain weight loss. The results suggest possibilities for simultaneous selection for high grain yield and storage insect pest resistance among drought-tolerant genotypes. Use of high-yielding and resistant maize hybrids to storage insect pest should be promoted for increased maize production and managing post-harvest losses due to the maize weevil in smallholder farming communities in Africa. Highlights: Currently there is no effective a single bullet strategy to address pre- and post-harvest production stresses due to insect damage in Africa. Fifty eight drought-tolerant experimental testcrosses hybrids were evaluated for agronomic performance and weevil resistance. Hybrids G56 (L49/T2) and G58 (L51/T2) had the least weevil damage and were rated as resistant to S. zeamais.